Victorian Alpine Plot Network (Alpine/sub alpine Australian Tundra Experiment): Vegetation Data, South-east Highlands, Australia, 2013–2014 - Ary Hoffmann (TERN Australia, 2014)
The Victorian Alpine Plot Network Vegetation Data Package contains vegetation data for four sites situated on the Bogong High Plains. Sites, which comprise multiple 1 square metre plots, are visited every second snow-free season. Vegetative growth is recorded in seven selected species, namely Carex breviculmis, Poa hiemata (Graminiods) and Celmisia pugioniformis, Erigeron bellidioides, and Plantago euryphylla (Forbs), and stems of Asterolasia trymalioides and Pimelea alpine by measuring growth amounts and converting measurements into a relative rate. This is part of a larger dataset that spans from during data collected in 2003 to document long-term effects of climate change (see methods for more information). The Victorian Alpine Plot Network research plots are revisited on a biannual basis , though measurements taken during surveys differ from visit to visit. A synopsis of related data packages which have been collected as part of the Victorian Alpine Plot Network’s full program is provided at http://www.ltern.org.au/index.php/ltern-plot-networks/victorian-alpine